Fabrication of individual alginate-TCP scaffolds for bone tissue engineering by means of powder printing. (6th January 2015) - Castilho, Miguel; Rodrigues, Jorge; Pires, Inês; Gouveia, Barbara; Pereira, Manuel; Moseke, Claus; Groll, Jürgen; Ewald, Andrea; Vorndran, Elke
Abstract: The development of polymer-calcium phosphate composite scaffolds with tailored architectures and properties has great potential for bone regeneration. Herein, we aimed to improve the functional performance of brittle ceramic scaffolds by developing a promising biopolymer–ceramic network. For this purpose, two strategies, namely, direct printing of a powder composition consisting of a 60:40 mixture of α / β -tricalcium phosphate (TCP) powder and alginate powder or vacuum infiltration of printed TCP scaffolds with an alginate solution, were tracked. Results of structural characterization revealed that the scaffolds printed with 2.5 wt% alginate-modified TCP powders presented a uniformly distributed and interfusing alginate TCP network. Mechanical results indicated a significant increase in strength, energy to failure and reliability of powder-modified scaffolds with an alginate content in the educts of 2.5 wt% when compared to pure TCP, as well as to TCP scaffolds containing 5 wt% or 7.5 wt% in the educts, in both dry and wet states. Culture of human osteoblast cells on these scaffolds also demonstrated a great improvement of cell proliferation and cell viability. While in the case of powder-mixed alginate TCP scaffolds, isolated alginate gels were formed between the calcium phosphate crystals, the vacuum-infiltration strategy resulted in the covering of the surface and internal pores of the TCP scaffold with a thin alginate film. Furthermore, the prediction of the scaffolds' critical fracture conditions under more complex stress states by the applied Mohr fracture criterion confirmed the potential of the powder-modified scaffolds with 2.5 wt% alginate in the educts as structural biomaterial for bone tissue engineering.